Application of Autologous Platelet-rich Plasma Exerts Cryoprotective Effects on Biological Characteristics of Human Oligoasthenoteratospermia Samples after Freezing and Thawing Procedures - Lorian, Keivan; Haghdani, Saeid; Vahidi, Serajoddin; Nabi, Ali (Urology Journal, 2024)
Purpose: Platelet-rich plasma (PRP) is enriched with active biological components which showed proliferative and cytoprotective properties in healing different injuries in medicinal fields. This study was designed to assess the cryoprotective effects of autologous PRP on the quality of oligoasthenoteratospermia (OAT) samples during freezing and thawing procedure. Materials and Methods: The present study is an experimental research. Twenty OAT semen samples were obtained from individuals and prepared by discontinuous density – gradients technique DGC). The control group is sperm samples after DGC. After the procedure, the specimen was divided into four groups. The Freeze group which has no additive and the other three groups were cryopreserved with different concentrations of PRP (1×105/ μL, 0.5×105/μL and 0.25×105/μL). Autologous PRP was provided by each participant. After thawing, sperm parameters, DNA fragmentation by sperm chromatin dispersion test (SCD), protamine deficiency by (Chromomycin A3) CMA3 staining, acrosome integrity and malondialdehyde (MDA) level were evaluated. Results: Cryopreservation resulted in a significant decrease in all factors compared to the control group. There were no significant changes in sperm count, morphology, non-progressive motility and acrosome reaction by adding PRP as a cryoprotectant in comparison with the freeze group. PRP at all three concentrations showed a significant increase in progressive motility (3.05 ± 2.01 vs. 14.05 ± 4.13, 12.35 ± 4.90 and 12.15 ± 9.65, P < 0.001) and viability (36.85 ± 10.25 vs. 47.85 ± 5.86, 51.30 ± 5.54 and 50.05 ± 5.67, P < 0.001) compared to the sperm samples without PRP. The percentage of immotile sperms decreased at all PRP concentrations compared to the freeze group. Moreover, PRP at 1×105/μL concentration showed cryoprotective effects on DNA fragmentation, protamine deficiency and MDA level compared to the other three concentrations. Conclusion: Cryopreservation and thawing procedures may exert adverse effects on biological factors of sperm samples. Therefore, adding PRP as cryoprotectant at all three concentrations especially 1×105/μL can be promising strategy to reduce adverse effects of cryopreservation on OAT samples.